KEPUTUSAN INVESTASI PEMILIK MODAL HOTEL BERBINTANG (Studi Kasus pada PT.”X” Pemilik Hotel “Y” Jember) - Chandra Setiawan Tri Yuwono (Universitas Muhammadiyah Jember, 2016)
Based on the growth rate of the hotel that indicated the level actual disbursement of credit showed a positive increase. The compositional in the Gross Regional Domestic Product (GRDP) shows an arrangement of the hotel GRDP lower than the Wholesale Retail GRDP, as well as the Restaurant GRDP. The occupancy rate of tourists, both foreign and domestic showed a significant decrease each year. With that data PT.